Outcome of combined surgical and intralesional steroids injection therapy for management of ear keloid - Bajracharya, Amir (Journal of Kathmandu Medical College, 2020)
Background: Ear keloid is one of the challenging problems that affect people of different races with substantial aesthetic outcomes. Various types of treatment modalities, including intralesional corticosteroid injection are advocated to lower recurrence following excision. Objectives: To investigate the efficacy of a combined excision and postoperative intralesional triamcinolone acetonide (TA) injection for treating ear keloid patients. Methodology: This was a descriptive study done to observe the outcome of combined approach of surgical and intra-lesional steroids injection therapy for ear keloids. Age, sex, site, size, duration, recurrence, and aesthetic outcome were evaluated. Results: A total of 18 patients representing 19 ear keloids, with one case having bilateral and 3 pediatric cases were included from February 2018 to January 2019.The mean age was 22 years with female to male ratio of 5:1, site were left sided 9 (50%), right 8 (44%) and 1(6%) bilateral. About 10 (53%) cases were at helix, and 9(47%) at ear lobule. Mean length of ear keloid was 1.53 cm with range of 0.5-3cm and mean breath 1.39cm with the range of 0.5-2.5 cm. The mean duration of ear keloid was 9.47 months. 2 (11%) cases showed a history of recurrence. Injection triamcinolone acetonide hypersensitivity was noted by 1 (5.3%) patient. Evaluation for all patients with aesthetic outcome was mean ± standard deviation (4.38±1.025). Conclusion: Management of ear keloid using the combination of surgical excision and intra-lesional steroids injection therapy can be a good alternative option with low recurrence rate.